2019
DOI: 10.1089/acu.2019.1352
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Percutaneous Electrical Nerve Stimulation of the Auricle for Relief of Postoperative Pain Following Cesarean Section

Abstract: Objective: Percutaneous electrical nerve stimulation is a nonpharmacologic modality of analgesia. This study was conducted to evaluate such a technology (ANSiStimÔ, DyAnsys Inc., San Mateo, CA) prospectively, in conjunction with standard analgesia per patient demand, for managing postoperative pain following lowersegment cesarean section. Materials and Methods: One hundred parturients were randomized into 2 equal groups (controls and study cases). The latter cohort consisted of parturients for whom nerve stimu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0
4

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 38 publications
(29 reference statements)
1
4
0
4
Order By: Relevance
“…A total of 145 studies were included, of which 126 were randomised controlled trials and 19 were systematic reviews and meta‐analyses (Fig. 1) [9–153]. The methodological quality assessments of the 126 randomised controlled trials included in the final qualitative analysis are summarised in online Supporting Information Table S1.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…A total of 145 studies were included, of which 126 were randomised controlled trials and 19 were systematic reviews and meta‐analyses (Fig. 1) [9–153]. The methodological quality assessments of the 126 randomised controlled trials included in the final qualitative analysis are summarised in online Supporting Information Table S1.…”
Section: Resultsmentioning
confidence: 99%
“…Several investigators reported on the beneficial effects of transcutaneous electrical nerve stimulation on pain scores, rescue analgesia use and patient satisfaction [126,127]. A study demonstrated that self-administered oral opioid analgesia was as effective as parenteral nurse-administered drugs [128].…”
Section: Postoperative Interventionsmentioning
confidence: 99%
“…kurz nachaVNS festgestellt werden. [14,31,67,74], n = 115), abdominale Eingriffe (4 Studien [1,7,15,45], n = 67), Tonsillektomie (1 Studie [35], n = 16), und Backenzahnextraktion (1 Studie [48], n = 48). Von diesen waren 7 Studien [7,31,35,45,48,67,74] randomisierte kontrollierte Studien (RCTs) hoher Qualität mit einer durchschnittlichen Bewertung von 7,1 aus 9 Punkten (.…”
Section: Ergebnisseunclassified
“…4). 2 weitere Studien [1,14] waren Fall-Kontrollstudien und 1 Studie [15] war eine Fallserie mit einer durchschnittlichen Bewertung von 3,8 Punkten.…”
Section: Ergebnisseunclassified
“…on the effect of TENS on reducing pain after cesarean section showed that TENS significantly reduced analgesic drug use by up to 50%, as well as the severity and duration of pain in the case group (13). Other studies have also generally shown the effect of TENS in reducing pain by up to 70% compared to not using it (14)(15)(16).…”
Section: Pnmt Gene Expressionmentioning
confidence: 96%